Entrepreneurial characteristics and business performance related to homestay business in Bandung, Indonesia - Irawan, Sandi; Supardi; Hasim, Muhammad Asyraf (International Journal of Psychosocial Rehabilitation, 2020)
The success of the homestay program is depending on the level of understanding of the customer requirements and the internal entrepreneurial characteristics. Service provider must at least meet some level of standard in terms of entrepreneur in order to perform in the industry. Most of the homestay is provided as an alternative to tourist in fulfilling their needs and wants towards experiencing the visited destination area. The homestay is one of the best options that can be offered to tourist to get closer to the community and local culture. As such there should be a right study on selecting the right entrepreneurial characteristics in order to perform in the business. Data were collected from 100 respondents in Bandung. Respondent was chosen among the stakeholder of the homestay. Respondent must at least be operating the homestay at this moment and willing to participate in the data collection voluntarily. The results indicate that entrepreneurial characteristics. Is important and worth to be evaluate before deciding to venture into the industry. The results show that entrepreneurial characteristics is part of the factors towards the success of business performance in the homestay industry.